Coexistence of Gait Disturbances and Chorea in Experimental Huntington’s Disease - João Casaca-Carreira; Yasin Temel; Marloes van Zelst; Ali Jahanshahi (Behavioural Neurology)
Huntington’s disease (HD) is an autosomal dominant neurodegenerative disease caused by an expanded CAG repeat. The clinical features are progressive motor dysfunction, cognitive deterioration, and psychiatric disturbances. Unpredictable choreic movements, among the most characteristic hallmarks, may contribute to gait disturbances and loss of balance in HD individuals. In this study, we aimed to investigate and characterize the gait abnormalities and choreic movements in a transgenic rat model of HD (tgHD). TgHD presents typical neuropathological, neurophysiological, and behavioral aspects mimicking some of the key features of human HD and is the only described experimental model for HD that exhibits choreiform movements. We used the Catwalk, with emphasis on static and dynamic gait parameters, to test the hypothesis that at symptomatic age (9 months) the dynamic measures of gait in HD are altered and coexist with choreiform movements. Our results showed that the dynamic parameters seem to be more affected than static parameters at this age in tgHD rats. The number of steps and step cycles and swing speed of the paws were increased in tgHD rat in comparison to wild-type controls. Our study demonstrates that gait abnormalities coexist with chorea rather than being caused by it. These symptoms may originate from distinct networks in the basal ganglia and downstream connections.